Цитоархітектоніка префронтальної кори щурів, які зазнали впливу холодового стресу - Іванська, К. М.; Мотузюк, Олександр Петрович; Міщенко, І. В.; Ivanska, K. M.; Motuziuk, Oleksandr P.; Mishchenko, I. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Досліджено цитоархітектоніку префронтальної кори щура після дії холодового стресу за допомогою загальноприйнятих гістологічних методів.У всіх ділянках префронтальної кори нейрони різні за будовою і функціональним значенням, утворюють шість шарів. Цингулярна кора стресованих тварин є тоншою, характеризується менш вираженою стратифікацією. Щільність розташування нейронів експериментальної групи зростає, а об’єм їх ядер зменшується, що вказує на негативну дію холодового стресу. Щільність клітин у порівнюваних шарах прелімбічної кори експериментальної групи зменшилася. У порівнянні з контрольною групою інфралімбічна (IL) кора стресованих тварин характеризується зменшенням товщини та найгірше вираженою стратифікацією на шари.

Аim: set the changes tsytoarhitektoniky prefrontal cortex of rats exposed to cold stress. Materials and methods. Investigated tsytoarhitektoniku prefrontal cortex of rats after cold stress. Results and conclusions. In all areas of the prefrontal cortex neurons are different in structure and functionality consists of six layers. Cingular (Сg) cortex is divided into two groups VI layers. Compared with controls, animals сingular bark that is exposed to stress thinner, characterized by less pronounced stratification. Density of neurons in the experimental group increases and decreases the volume of their nuclei, indicating a negative effect of cold stress. Thickness prelimbic (PrL) crust experimental group significantly decreased compared with the control group. The density of cells in the cortex compared layers prelimbic experimental group decreased. Neurons experimental group experienced adverse changes: vacuolization of the cytoplasm, hyperchromatic nuclei staining, shrinkage and reduce the volume of the nucleus suggests that the ability to function. Compared with the control group Infralimbic (IL) cortex animals are exposed to stress is characterized by a decrease in thickness and the worst pronounced stratification into layers. Volume neurons experimental group of animals and their density has not changed.
Tsytoarhitektonika prefrontal cortex of rats exposed to cold stress
Keywords: кора; прелімбічна кора; інфралімбічна кора; холодовий стрес; anterior cingulate (Сg); prelimbic prefrontal cortex (PrL); Infralimbic prefrontal cortex (IL); cold stress